Análise retro-tecno-econômica de uma planta de produção de amônia baseada na gaseificação de resíduo sólido urbano - Paixão, Vitor Pirovani (2018)
Municipal Solid Waste (MSW) is generated yearly in enormous amount worldwide. The treatment and the final disposal of this waste is both financially and environmentally expensive. Also environmetally agressive, the NH3 production process, which is based primarely on the CH4 steam reform, releases great amounts of CO2 in the atmosphere. However, the NH3 production process has extreme importance to the world’s economy due to its use as raw material for the manufacture of several chemicals, especially nitrogen fertilizers. Therefore, the NH3 production is even more important to countries which depend on agricultural production such as Brazil. Aiming a more sustainable alternative, in this work a retro-techno-economic analysis of an NH3 production plant that uses the gases generated during the MSW gasification is done. The plant is designed to recieve MSW generated by 100,000 people. The plant capacity is 21.25 tons of NH3 per day. The NH3 minimum selling price for a project life of 20 years with an internal rate of return of 15% was calculated to be US$ 2,262.30/ton. This value is approximated 8 times higher than the current market price. Nevertheless, the use of the MSW generated by a population ranging from 550,000 to 1,500,000 people, setting the NH3 minimum selling price to average price from the last decade, results in an Internal Rate of Return (IRR) ranging from 0% to 4%. Although this IRR is not attractive for private investors, its implementation could reduce the public expenditure since the municipalities are obligated by the law to appropriately treat this residue. In addition, jobs would be created, NH3 would not be generated from a fossil fuel source and greenhouse gas emissions due to municipal solid waste decomposition, mainly CH4, would be reduced.